JUSTIFICATION OF THE COMPOSITION OF THE POLYMER COMPOSITE MATERIAL WITH FUNGICIDAL PROPERTIES - KACHAN, ROMAN; PETROVA, LESYA; PROHORENKО MARIA; SOBOLEVA, KATERINA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper analyzed the forms of polymer composite agents that can be used for the prevention and complex treatment of onychomycosis. As you know, there are many soft forms for the prevention and treatment of fungal infections: creams, ointments, gels, varnishes and plasters. Cream-like substances are easily absorbed, but are not able to penetrate deep into the tissues. The gel is a medicinal form that does not contain fats and oils, its acid-alkaline parameters are close to those of the skin. It is easily distributed on the skin, quickly absorbed, does not clog pores. However, gels are easily wiped off and washed off with water, accordingly, they cannot have prolonged fungicidal activity on the surface of the nail. Ointment is a medicinal form based on fats. It is absorbed more slowly than gel-like and cream-like preparations, but it works longer. Penetrates deeply. It is applied to dry surfaces, scars, seals. Smeared areas can be covered with bandages. It is inconvenient to use this shape on the nail. A patch is a medicinal form that can be a solid or a liquid form of the drug according to its aggregate state. According to the degree of dispersion of the plaster mass, they can be alloys, solutions, suspensions, emulsions or combined systems. An effective form for the treatment of onychomycosis. But it has one significant drawback when applied to the nail - aesthetics. Varnish is a medicinal form intended for application to fingernails and toenails. Any typical modern nail polish contains four main types of ingredients: polymer, solvent, plasticizer and active ingredient. After applying the varnish, the active substance penetrates into the nail plate and then into the nail bed, where it begins to act. It has been established that the most optimal form is varnish. Film formers, which can potentially be used as part of a polymer composite drug with fungicidal properties, were also studied. The expediency of using nitrocellulose and acrylate copolymer as a film-forming varnish with fungicidal properties is substantiated. 12 variants of varnish compositions with fungicidal properties based on these substances are offered.